2011
DOI: 10.1007/s12105-011-0303-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma Arising from the Tongue of an 11-Year-Old Girl with Xeroderma Pigmentosum

Abstract: Xeroderma pigmentosum (XP) is a rare autosomal recessive defect in DNA endonuclease activity that is associated with the development of cutaneous malignancies, at sun exposed sites, including basal cell carcinoma, squamous cell carcinoma, and melanoma. Squamous cell carcinomas are also known to target the anterior tongue. Patients sometimes develop angiosarcomas, and these invariably arise from sun-exposed skin. A biopsy was taken from a large mass arising in the anterior tongue of an 11-year-old girl with XP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
1
15
0
2
Order By: Relevance
“…A 15-year-old female from the Central African Republic presented with a history of XP and multiple tumors on the face, including BCC and melanoma in addition to angiosarcoma of the tongue (the pathologic findings of the tongue neoplasm have previously been reported) [8]. The patient first presented at the age of 10 with no light perception vision in the right eye and 20/40 in her left eye.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 15-year-old female from the Central African Republic presented with a history of XP and multiple tumors on the face, including BCC and melanoma in addition to angiosarcoma of the tongue (the pathologic findings of the tongue neoplasm have previously been reported) [8]. The patient first presented at the age of 10 with no light perception vision in the right eye and 20/40 in her left eye.…”
Section: Resultsmentioning
confidence: 99%
“…A preneoplastic spectrum known as conjunctival intraepithelial neoplasia (CIN), classified as mild, moderate, or severe depending on the depth of conjunctival epithelial dysplasia, can also present secondary to sun exposure with this underlying genetic disorder [3,4]. Other skin tumors including keratoacanthoma and fibrosarcoma [3] as well as angiosarcoma of the tongue have been additionally reported [8]. Atypical fibroxanthoma (AFX) is a benign tumor seen in previously sun-damaged skin of the head and neck in the elderly [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Lesions were located at the tip of the tongue in eight cases and the dorsal tongue was affected in the remaining three . Olson et al reported an angiosarcoma at the tip of the tongue of a patient with XP.…”
Section: Discussionmentioning
confidence: 99%
“…Angiosarcoma is a xeroderma pigmentosum related tumor that usually arises in sun-exposed skin but can also arise in the oral cavity [5]. Angiosarcoma is one of the rarest tumors arising in the tongue, accounting for vanishingly small proportion of primary tongue sarcomas.…”
Section: Discussionmentioning
confidence: 99%